Designing e-Book of Basic Physics Fluid Series with Assistant of Virtual Laboratory to Improve Critical Thinking Skills - Habibbulloh, Muhammad; Satriawan, Muhammad; Zakaria, Azar; Sya'roni, Imam (Physics Education Research Journal, 2024)
This study aims to develop the e-book Basic Physics Fluid Series design assisted by virtual laboratory Tracker Video Analysis (TVA) that effectively improves students' critical thinking skills. The method used in this study is Research and Development. The graphic design developed, including illustrations and visual elements, was identified as necessary for improving critical thinking skills. At the same time, practice questions with varying difficulty levels allowed students to apply knowledge. The validation process, including the Content Validity Ratio (CVR) test, underlined high agreement and validity, with suggestions for improvement, including contextual design, material optimization, interactive elements, accessibility considerations, student feedback collection, and curriculum alignment. The test results showed that learning with this e-book effectively improved students' critical thinking skills. The results obtained in the indicator provided a simple explanation, concluding that it shows a high N-gain value. In contrast, several other indicators show moderate values. This e-book design can be a role model for developing similar media, especially related efforts to improve students' Critical Thinking Skills (CTS).